(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2026)
Rapid urbanisation in Nigeria has intensified waste generation and exposed the limits of disposal-oriented waste management systems. While circular economy (CE) principles are increasingly referenced in policy discussions, their practical scaling remains limited. This study examines the systemic barriers constraining the expansion of circular economy practices in Awka, Enugu, and Onitsha in south-eastern Nigeria. Using a qualitative exploratory design, twelve focus group discussions were conducted with municipal officials, private recycling firms, informal waste actors, and community representatives. Thematic analysis revealed six interrelated barriers: regulatory fragmentation, infrastructural deficits, financial constraints, informal–formal disconnects, weak market demand, and institutional coordination gaps. Findings indicate that circular transition is not hindered by the absence of recovery activity, but by structural misalignments across governance, infrastructure, finance, and market systems. Disposal-oriented regulatory incentives reinforce mixed waste streams, while limited access to capital and unstable demand discourage technological upgrading and private investment. Informal actors, despite playing a central role in material recovery, remain institutionally excluded. Cross-city comparisons further demonstrate that administrative structure and commercial intensity shape transition dynamics. The study concludes that scaling circular economy practices in Nigerian cities requires coordinated governance reform, infrastructural investment, financial innovation, and inclusive institutional frameworks rather than isolated technical interventions.